Unpacking the African continental free trade area: A glossary - International Trade Centre (ITC) (International Trade Centre (ITC), 2023)
This glossary is the first edition of legal and other terms that micro, small and medium enterprises (MSMEs) will encounter while trading under the African Continental Free Trade Area (AfCFTA). The aim of the glossary is to help users understand legal, commercial and customs terms found in the AfCFTA Agreement as it has been crafted with inputs and guidance from the African private sector, including MSMEs, women and youth entrepreneurs, and business support institutions striving to improve the African business environment.
Keywords: AfCFTA; Glossaire; Lexique; ZLECAf

Les Communautés économiques régionales, améliorent-elles le commerce intrarégional dans le cadre de la ZLECAf ? - El Bekri, Hafsa (Revue Interventions économiques, 2023)
Cet article examine l’impact des facteurs de proximité sur l’intensité commerciale intra africaine. Dans le cadre des modèles reposant sur une approche ex post, notre contribution concerne l’usage d’un modèle de gravité avec la prise en compte des distances géographiques et économiques. Nos résultats montrent que les niveaux d’intégration commerciale contrastés au sein des CER risquent d’accentuer l’asymétrie d’intégration continentale, ils révèlent que la distance économique impacte positivement et significativement l’intensité des échanges et suggèrent le renforcement de l’intégration via les chaines de valeur régionales. This article examines the impact of proximity factors on intra-African trade intensity. Our contribution consists of the use of a gravity model with the consideration of geographical and economic distances. Our results show that the contrasting levels of trade integration within the RECs are likely to accentuate the asymmetry of continental integration, they reveal that economic distance has a positive and significant impact on the intensity of trade and suggest the strengthening of integration through regional value chains.
Keywords: AfCFTA; Afrique; Bilateral intensities; Commerce intra-régional; Communautés économiques régionales; Facteurs de proximité; Intra-African trade; Modèle de gravité; Proximity factors; Regional integration